RESEARCH NOTES Examining the Impact of Customer-To-Customer Interaction on Service Experiences: A Pilot Study (Malaysian Management Journal, 2015)
This research focuses on how the design of backpacker hostels influences social interaction among guests and how this could enhance or spoil their service experience. There are opposing views on how different aspects of hostel design and services contribute towards guests’ evaluation of their hostel stay. On one hand, it is suggested that a hostel environment which encourages social interaction adds value to the service experience while on the other hand, an environment that offers extra privacy, such as en-suite bedrooms, is more valued. The present research therefore argues that some aspects of the hostel’s current design and core services may now be redundant for certain market segments of the hostel guest. Empirical evidence is needed to illustrate the extent to which hostels are providing the right design and services to meet the current requirements of their target market. At this stage of the research, a pilot study has been carried out using semi-structured interviews with individuals who have stayed in backpacker hostels. Using the Critical Incident Technique (CIT), respondents were asked to recall a specific incident where they had interacted with other hostel guests. Details about the environment in which the interaction took place, as well as how the respondents felt about the interaction, were asked during the interview. It is expected that the findings of this research will shed light on which aspects of a hostel’s design and guests’ interaction would contribute towards enhancing the service experience.